Complex Thinking: How are Students' Mathematical Problem-Solving Skills in Elementary School? - Fauzi, Irfan; Rakhmat, Cece; Budiman, Nandang (CV. Creative Tugu Pena, 2023)
This study aims to see an overview of students' mathematical problem-solving skills in elementary school. This study uses a quantitative approach with a descriptive method. The subjects in this study amounted to 25 grade 5 students in one of the elementary schools in Bandung with details of 10 male and 15 female students. The data collection technique used is a mathematical problem-solving test instrument based on Polya theory on fractional concept material. The data analysis carried out was to calculate descriptive statistics using Microsoft excel and SPSS version 24 to see an overview of mathematical problem-solving skills, categorization of problem-solving scores based on high, medium, and low, and the achievement of students' mathematical problem-solving indicators. From these data, it is then analyzed in depth and linked with relevant theories. The results of this study showed that based on the categorization of student scores, 4 students were in the high category, 15 students were in the medium category, and 6 students were in the low category. The indicator that has a high percentage of students mastered is understanding the problem at 73%, and the lowest indicator at re-checking is 44%. This research can contribute to efforts to create meaningful learning in mathematics by involving complex thinking skills including mathematical problem-solving skills. Keywords: Complex Thinking, Mathematical Problem-Solving Skills, Elementary School